Studi Kelayakan Investasi Pengembangan UMKM di Sektor Kuliner - Akhmad Mubadilah; Ika Hartika; Sri Juminawati; Eva Yuniarti Utami; Dewi Mariam Widiniarsih (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The purpose of this study is to analyze the feasibility study of investment in developing MSMEs in the culinary sector. The objects of this study are from the aspect of business feasibility studies, namely: 1) Marketing aspects; 2) Legal aspects; and 3) Social and economic aspects. The study of business feasibility analysis in culinary MSME businesses uses qualitative research methods which are carried out in analyzing and assessing the feasibility of developing a business. Qualitative data obtained based on the results of interviews and observations. The results of this study found that the development of culinary MSMEs has great potential, especially with the right marketing approach, a deep understanding of market potential, and a mature investment feasibility analysis. In conducting a feasibility study, it is important to consider marketing aspects, market potential, and realistic financial analysis so that culinary businesses can develop and compete sustainably. The feasibility study of investment in the development of MSMEs in the culinary sector provides a clearer picture of business prospects, the risks involved, and the potential profits that can be obtained.